The impact of anonymous marking on students' perceptions of fairness, feedback and relationships with lecturers. Issue 7 (3rd October 2018) - Pitt, Edd; Winstone, Naomi
Abstract: Anonymity in marking is a contentious issue within higher education. Conflicting research findings have identified issues surrounding gender bias, ethnicity bias and fairness in marking. However, the effects of anonymity upon feedback mechanisms have not been systematically explored. This study sought to understand the effects of anonymous marking and feedback upon students' perceptions of its potential for future learning and relationship building with their lecturers. First year United Kingdom undergraduate business, politics, pharmacy and french students experienced anonymous and non-anonymous marking of coursework across different modules. Student performance data were collected, and a survey was administered following the completion of their modules. Results revealed that anonymous marking did not seem to advantage or disadvantage particular groups of students in terms of grade outcome. There was no significant difference in perceptions of fairness according to whether or not marking was anonymous. Furthermore, the results suggest that anonymous marking might undermine the learning potential of feedback, and minimise the strength of the relationship between lecturers and students, which may minimise the role of dialogue in the feedback process.